A history of Russia. Part 1 from Peter the Great to Gorbachev - Steinberg, Mark D. 1953-; Teaching Company Limited Partnership (Chantilly, Va. Teaching Co., 2003)
Twelve 30 minute lectures by Mark Steinberg on the history of Russia.
disc 1. lecture 1. Understanding the Russian past ; lecture 2. The Russia of Peter the Great's childhood ; lecture 3. Peter the Great's revolution ; lecture 4. The Age of empresses - Catherine the Great ; lecture 5. Social rebellion - The Purgachev uprising ; lecture 6. Moral rebellion - Nikolai Novikov -- disc 2. lecture 7. Alexander I - Imagining reform ; lecture 8. The Decembrist rebellion ; lecture 9. Nicholas I - Orthodoxy, autocracy, nationality ; lecture 10. Alexander Pushkin, Russia's national poet ; lecture 11. The birth of the intelligentsia ; lecture 12. Westernizers - Vissarion Belinskii --
Title from disc label.
DVD
Keywords: Russia -- History; Educational films; Filmed lectures; Nonfiction films